Needs Analysis of Natural, Cultural, and Arts Tourism Potency - Luqman Al Hakim; Siti Supeni; Leticia Juliena Aji; Attharik Bowi Rinugroho; Sulistiawan Sulistiawan; Yanu Arfianto (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
Purpose: the study aims at analyzing the needs of natural, cultural, and arts tourism destination at Plesungan Tourism Village, Gondangrejo, Karanganyar. There are four objects being observed and analyzed before doing community service. Research methods: the type of research is descriptive study. The subjects of research are the head of four tourism objects at Plesungan Village. They are Plesungan Waterpark, Meteor Putih Hermitage, Lemah Putih Hermitage, and Waste Management Tool. The methods in collecting the data are an interview, observation, and documentation. The data were analyzed through data display, data reduction, and conclusion. Results and discussions: the findings of research are the needs of promotion to improve the quantity of visitors, there is a necessity of serving local food and beverages as well as preserving local heritage, there are no souvenirs from the village that empower local potency, the necessity of healthy life training during the pandemic, and the English skill of the villagers need to be improved to facilitate foreign tourists while visiting the village. Conclusion: empowering local potency to facilitate tourists is the main needs of the village to preserve and improve the quality of tourism service and the quantity of visitors.